Synergetic monitoring of pressure and temperature stimulations in multisensory electronic skin based on time decoupling effect - Zhiyi Gao; Ye Zhang; Zhenyu Hu; Dongdong Zhang; Shengbin Li; Huiyun Xiao; Ziyin Xiang; Dan Xu; Haifeng Zhang; Yuanzhao Wu; Yiwei Liu; Jie Shang; et al. (Carbon Energy)
Abstract The progress from intelligent interactions requires electronic skin (E‐skin) to shift from single‐functional perception to multisensory capabilities. However, the intuitive and interference‐free reading of multiple sensory signals without involving complex algorithms is a critical challenge. Herein, we propose a flexible multisensory E‐skin by developing a highly homogeneous dispersion of BaTiO3 nanoparticles in polydimethylsiloxane dielectric layer. The E‐skin is sensitive to externally applied pressure as well as temperature and can distinguish dual synergetic stimuli by the time decoupling effect. The pressure and temperature perception was achieved in an individual device, which greatly reduced the structural complexity compared with multifunctional integrated devices. The sensitivity of E‐skin for pressure detection is as high as 0.0724 kPa−1 and the detection range reaches as wide as 15.625–10 MPa. The sensitivity to temperature detection is as high as −1.34°C−1 and the detection range reaches 20–200°C. More importantly, by equipping with a multilayer neural network, the evolution from tactile perception to advanced intelligent tactile cognition is demonstrated.